2013
DOI: 10.1002/j.2334-5837.2013.tb03034.x
|View full text |Cite
|
Sign up to set email alerts
|

1.2.2 Closing the loop for lifecycle product management in Norwegian subsea systems

Abstract: Systems that we deploy in subsea natural environments face many of the same challenges as space-based systems. This means that they are complex and often embedded as systems of systems. Norwegian firms excel in this industry and are increasingly applying systems engineering processes to ensure the success of their projects. However, these processes are defined as product development activities that do not accommodate the full product lifecycle. This paper investigates the project execution processes of a Norwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The focus in the industry has been on delivering high volume as fast as possible, without the concern of the high cost following inefficient development. However, after the downturn, the industry is looking towards systems engineering to improve their offering [18]. Even though subsea companies are increasingly applying systems engineering methods and recognizing their value, implementing new work processes in mature organizations is challenging [19,20].…”
Section: Systems Engineering In the Oil And Gas Industrymentioning
confidence: 99%
“…The focus in the industry has been on delivering high volume as fast as possible, without the concern of the high cost following inefficient development. However, after the downturn, the industry is looking towards systems engineering to improve their offering [18]. Even though subsea companies are increasingly applying systems engineering methods and recognizing their value, implementing new work processes in mature organizations is challenging [19,20].…”
Section: Systems Engineering In the Oil And Gas Industrymentioning
confidence: 99%
“…The focus on system engineering in the oil and gas industry is growing, and the establishment of the Incose Oil and Gas working group in 2016 is a proof of this. The Norwegian subsea industry is increasingly applying systems engineering process to ensure success of their projects (Mjånes, Haskins & Piciaccia, 2012). Wee and Muller (2016) states that the supplier company typically uses a project execution model built on the Vee model.…”
Section: Systems Engineering In Subsea Industrymentioning
confidence: 99%
“…Previous research [17] found that requirements definition and requirement analysis is not explicitly defined by the PEM. The requirement definition takes place as part of the contract agreement, which is negotiated separately from the PEM.…”
Section: Figure 2 Akso Pem Feasibility and Concept Phasementioning
confidence: 99%
“…The optimization of subsea coolers was approached using the company customized project execution model (PEM), which is loosely based on the SE vee-model [17]. Use of the PEM was augmented by Use Case Analysis (UCA) and Analytical Hierarchy Process (AHP).…”
Section: Introductionmentioning
confidence: 99%